2007
DOI: 10.1083/jcb.200701134
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of PI3-kinase and phospholipase A2 in Dictyostelium discoideum chemotaxis

Abstract: Chemotaxis toward different cyclic adenosine monophosphate (cAMP) concentrations was tested in Dictyostelium discoideum cell lines with deletion of specific genes together with drugs to inhibit one or all combinations of the second-messenger systems PI3-kinase, phospholipase C (PLC), phospholipase A2 (PLA2), and cytosolic Ca2+. The results show that inhibition of either PI3-kinase or PLA2 inhibits chemotaxis in shallow cAMP gradients, whereas both enzymes must be inhibited to prevent chemotaxis in steep cAMP g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
99
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 31 publications
0
99
0
Order By: Relevance
“…Through mutagenesis and combinational chemical inhibitor assays, PLA was shown to function in the chemotaxis pathway in Dictyostelium, where the PLA pathway is parallel to the PI3K pathway. Upon inhibition of both pathways, a severe defect of chemotaxis occurs in Dictyostelium in response to the cAMP gradient (39,40). The co-existence of these redundant pathways allows cells greater flexibility to respond to different environmental circumstances, such as gradients of high or low steepness.…”
Section: Discussionmentioning
confidence: 99%
“…Through mutagenesis and combinational chemical inhibitor assays, PLA was shown to function in the chemotaxis pathway in Dictyostelium, where the PLA pathway is parallel to the PI3K pathway. Upon inhibition of both pathways, a severe defect of chemotaxis occurs in Dictyostelium in response to the cAMP gradient (39,40). The co-existence of these redundant pathways allows cells greater flexibility to respond to different environmental circumstances, such as gradients of high or low steepness.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that a parallel pathway for F-actin polymerization and chemotaxis must function independently of PIP 3 formation (Figure 4). Two independent research groups have now identified PLA 2 as an alternative mediator of chemotaxis (Chen et al, 2007;van Haastert et al, 2007;Figures 4,5). PLA 2 catalyzes the cleavage of phospholipids into fatty acids (e.g.…”
Section: Pla 2 -Signalingmentioning
confidence: 99%
“…For each concentration, the WT response is arbitrarily set to 100. Data are adapted and summarize the work of multiple groups (Chen et al, 2007;van Haastert et al, 2007;Hoeller and Kay, 2007;Takeda et al, 2007). Chemotaxis of polarized Dictyostelium to 1 μM cAMP.…”
mentioning
confidence: 99%
“…In chemoattraction, PLA2 is also involved in directional sensing but its role in chemorepulsion is unknown (Chen et al, 2007;Takeda et al, 2007;Van Haastert et al, 2007). While results have shown that PI3K is not essential for a cell to exhibit chemoattractive migration, it has been found to be necessary for a chemorepulsive response in the experimental studies performed .…”
Section: Introductionmentioning
confidence: 97%